Why this app? How educators choose a good educational app. (July 2022) - Montazami, Armaghan; Ann Pearson, Heather; Kenneth Dubé, Adam; Kacmaz, Gulsah; Wen, Run; Shajeen Alam, Sabrina
Abstract: The study examines if educators are valuing certain benchmarks of quality (i.e., scaffolding, feedback, curriculum, development team, learning theory) when they select educational apps from app stores and evaluates how they gather information during the selection process. Pre-service and working elementary educators viewed and evaluated app store pages for 10 simulated apps while gaze data (i.e., looking at either the written descriptions or app images) were collected using an eye-tracker. Participants' value-judgements were measured by their willingness to download the app, how much they would pay, their rating, and ranking, while gaze data examined participants' fixation count and fixation duration. Results from paired-samples t -tests, repeated-measures ANOVAs, and nonparametric tests indicate that educators value apps with educational benchmarks over buzzwords, while judging apps with development team, scaffolding, and curriculum higher than those with an integrated learning theory and feedback. Moreover, eye tracking results revealed that educators scrutinize app images more when they feature educational benchmarks. To improve educators' app selection, professional development should target educators' views of learning theory and feedback as well as their use of app images as a source of information on app quality (cf., detailed text descriptions). Highlights: An eye tracking study of how educators select educational apps from app stores to determine which apps they value. Educators value apps containing research-based educational benchmarks over buzzwords. Learning theory and feedback are the least valued educational benchmarks. Educators spend more time evaluating text descriptions of apps than studies previously reported. The apps educators selected reflect their knowledge of evidence-based educational practice.